Globalization Drives Strategic Product Switching - Moreno Badia, Marialuz; Beveren, Ilke Van.; Slootmaekers, Veerle (Washington, D.C. : International Monetary Fund, 2008)
Using firm-level data for Estonia for the years 1997-2005, we analyze the impact of international competition on firm dynamics, considering both firm closedown and product switching. We contribute to the literature in two important ways: (1) this is the first paper to study the determinants of exit and product switching in an emerging market; and (2) we consider explicitly the role of export opportunities. Our results indicate that globalization does not affect firm exit significantly but it is an important factor explaining product switching. Previous studies on industrial countries have shown that product switching has been a defensive strategy against low-cost imports. In contrast, our results suggest that Estonian firms have switched products as an offensive strategy to take advantage of the export opportunities created by trade liberalization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet